Studying State Development through the Archive: The Case of Interwar Turkey - Aykiz Dogan (Revue Internationale des Études du Développement)
What methodological insights can archival research bring for a global historical sociology of developed (or “undeveloped”) states within asymmetrical geopolitical contexts? This article proposes a methodological approach centred on the “Archive” as a site of production of development visions, knowledge and representations. Focusing on a case study of interwar Turkey, the article explores possible historical sources for a multi-level analysis linking state (trans)formation with development and situating it within its global context, where national and international orders are co-constructed with modernist visions. It argues that cross-referencing national and international archives reveal the interconnectedness of local and global dynamics in state development, transcending methodological nationalism and Eurocentric perspectives.